2022
DOI: 10.1111/jerd.12954
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis accuracy of fit on 3D‐printed casts versus stone casts: A comparative study in the anterior maxilla

Abstract: Objective To compare in vitro the accuracy of fit of a reference prosthesis seated on three‐dimensional (3D) printed casts generated from digital implant scans vs stone casts made by conventional implant impressions. Material and Methods A partially edentulous maxillary master cast with two internal connection implants was generated, while a reference implant‐supported prosthesis was fabricated. Conventional splinted open‐tray impressions were taken to create stone casts (n = 10) (control group). A digital sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…The 3D printed implant analog models' evidence was analyzed with 11 in vitro studies (Abdeen et al, 2022;Alshawaf et al, 2018;Banjar et al, 2021;Buda et al, 2018;Jin et manufacture implant analog models were MultiJet, SLA, DLP, and CLIP. The 3D printing parameters reported in the studies were the layer thickness, the angulation to the printing platform, and the characteristics of the printing cast base.…”
Section: Rq2: "Regarding Static Guided Surgery In Dental Implant What...mentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D printed implant analog models' evidence was analyzed with 11 in vitro studies (Abdeen et al, 2022;Alshawaf et al, 2018;Banjar et al, 2021;Buda et al, 2018;Jin et manufacture implant analog models were MultiJet, SLA, DLP, and CLIP. The 3D printing parameters reported in the studies were the layer thickness, the angulation to the printing platform, and the characteristics of the printing cast base.…”
Section: Rq2: "Regarding Static Guided Surgery In Dental Implant What...mentioning
confidence: 99%
“…The role played by different printing parameters were analyzed in the study of Jin et al (2022) with a DLP printer and determined that a hollow inner cast base and a layer thickness of 100 μm maximized the accuracy of the implant analog final position. Abdeen et al (2022), Mathey et al (2021), and Tas et al (2022) reported that the full digital workflow, with digital implant impressions and 3D printed implant analog models, showed statistically significantly lower 3D deviations than plaster models generated from conventional implant impressions Abdeen et al (2022). printed solid implant model bases instead of hollow bases, also with 100 μm layer thickness, with a CLIP printer (M2 Carbon), a SLA printer (Form 3b, Formlabs), and a DLP printer (Varseo S, BEGO).…”
mentioning
confidence: 99%